Cloaking strategy for Love waves. (January 2022) - Chatzopoulos, Z.; Palermo, A.; Guenneau, S.; Marzani, A.
Abstract: Love waves are antiplane elastic waves which propagate along the surface of a heterogeneous medium. Under time-harmonic regime, they are governed by a scalar equation of the Helmholtz type. We exploit the invariance of this governing equation under an in-plane arbitrary coordinate transformation to design broadband cloaks for surface defects. In particular, we apply transformation elastodynamics to determine the anisotropic, position dependent, mechanical properties of ideal cloaks able to hide triangular and parabolic-shaped defects. Dispersion analysis and time-harmonic numerical simulations are employed to validate the proposed strategy. Next, we utilize layered monoclinic materials, with homogenized properties matching those of the ideal cloaks, to design feasible triangular-shaped cloaks. The performance of the layered cloaks is validated via parametric analysis of the dispersion curves, which converge to those of the ideal cloak when the unit cell-wavelength ratio vanishes. Finally, time-harmonic numerical simulations confirm a significant reduction of the defect-generated scattered fields by the layered cloaks.